Pathways of apoptosis in muscle 2 - Alway, Stephen E. (Henry Stewart Talks, 2018)
Satellite cells and apoptotic signaling in aging muscle, MicroRNA regulation of apoptotic signaling in aging muscle, Interventions in apoptotic signaling (denervation vs. exercise), Nutritional & hormonal modulators of apoptosis signaling pathways in muscle wasting in aging